The tragedy of the commons and inflation bias in the euro area - Valeriya Dinger; Sven Steinkamp; Frank Westermann (Center for Economic Studies and ifo Institute (CESifo), 2012)
Central bank credit has expanded dramatically in some of the euro area member countries since the beginning of the financial crisis. This paper makes two contributions to understand this stylized fact. First, we discuss a simple model of monetary policy that includes (i) a credit channel and (ii) a common pool problem in a monetary union. We illustrate that the interaction of the two elements leads to an inflation bias that is independent of the standard time-inconsistency bias. Secondly, we present empirical evidence that is consistent with the view of fragmented monetary policy and changing policy objectives among the national cen-tral banks in the euro area. We show that after 2007, central bank credit has been highly correlated with unemployment, but not with inflation in the respective countries.
Keywords: E52; E58; H41; 330; tragedy of the commons; inflation bias; credit channel; TARGET2; euro area; Geldpolitik; Kreditkanal; Europäische Wirtschafts- und Währungsunion; Gemeingüter; Inflation; Eurozone